Restarting tourism, travel and hospitality: The day after - Evangelos Christou; Anestis Fotiadis; Kostas Alexandris (International Hellenic University, 2021)
Book of extended abstracts (proceedings) of TOURMAN 2021 Conference "Restarting tourism, travel and hospitality: The day after".
Keywords: Z32; Z33; L83; M1; 330; tourism; hospitality; leisure; travel; marketing; management